Abitur 2014 - Geographie Prüfungsaufgaben mit Lösungen - Böker, Sandra; Koch, Rainer; Lage, Wolfgang; Wagner, Torsten (Abitur NRW Geographie Gymnasium, Gesamtschule, 2013)
Original-Prüfungsaufgaben Abitur 2013